The First Frontier: Digital Biomarkers for Neurodegenerative Disorders - Dorsey, E. Ray; Papapetropoulos, Spyros; Xiong, Mulin; Kieburtz, Karl (Digital biomarkers, 2017)
Current measures of neurodegenerative diseases are highly subjective and based on episodic visits. Consequently, drug development decisions rely on sparse, subjective data, which have led to the conduct of large-scale phase 3 trials of drugs that are likely not effective. Such failures are costly, deter future investment, and hinder the development of treatments. Given the lack of reliable physiological biomarkers, digital biomarkers may help to address current shortcomings. Objective, high-frequency data can guide critical decision-making in therapeutic development and allow for a more efficient evaluation of therapies of increasingly common disorders.